(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis examines the portrayal of female identity in Anni Erno (Annie Ernaux)’s autobiographical narrative Une femme (“A Woman’s Story,” 1987). Drawing on Bourdieusian sociology and feminist literary criticism, the study analyses how Ernaux constructs womanhood through the prism of the mother-daughter relationship, class mobility, and collective memory. The author argues that Une femme transcends conventional autobiography by transforming one working-class woman’s life into a transpersonal document of gendered social existence in twentieth-century France, and that Ernaux’s écriture plate (flat writing) is a politically motivated refusal to aestheticise the lives of dominated women.